Feasibility study of a lead(II) iodide-based dosimeter for quality assurance in therapeutic radiology. (14th September 2017) - Heo, Y.J.; Kim, K.T.; Oh, K.M.; Lee, Y.K.; Ahn, K.J.; Cho, H.L.; Kim, J.Y.; Min, B.I.; Mun, C.W.; Park, S.K.
Abstract: The most widely used form of radiotherapy to treat tumors uses a linear accelerator, and the apparatus requires regular quality assurance (QA). QA for a linear accelerator demands accuracy throughout, from mock treatment and treatment planning, up to treatment itself. Therefore, verifying a radiation dose is essential to ensure that the radiation is being applied as planned. In current clinical practice, ionization chambers and diodes are used for QA. However, using conventional gaseous ionization chambers presents drawbacks such as complex analytical procedures, difficult measurement procedures, and slow response time. In this study, we discuss the potential of a lead(II) iodide (PbI 2 ) -based radiation dosimeter for radiotherapy QA. PbI 2 is a semiconductor material suited to measurements of X-rays and gamma rays, because of its excellent response properties to radiation signals. Our results show that the PbI 2 -based dosimeter offers outstanding linearity and reproducibility, as well as dose-independent characteristics. In addition, percentage depth dose (PDD) measurements indicate that the error at a fixed reference depth D max was 0.3%, very similar to the measurement results obtained using ionization chambers. Based on these results, we confirm that the PbI 2 -based dosimeter has all the properties required for radiotherapy: stable dose detection, dose linearity, and rapid response time. Based on the evidence of this experimental verification, we believe that the PbI 2 -based dosimeter could be used commercially in various fields for precise measurements of radiation doses in the human body and for measuring the dose required for stereotactic radiosurgery or localized radiosurgery.